Assessing Adherence to Lifestyle Changes in Patients with Type 2 Diabetes: A Comprehensive Assessment of Psychological, Social and Clinical Determinants - Chunli, Liu; Zain, Zarihah Mohd; Malek, Azma Abdul (Journal of Ecohumanism, 2024)
Purpose: This study aims to systematically evaluate the multidimensional determinants of lifestyle change compliance in patients with type 2 diabetes, establish a prediction model integrating psychological, social and clinical characteristics, and provide a theoretical basis for the development of personalized intervention strategies. Methods: Mixed research methods were used, including cross-sectional questionnaire survey (n=300) and in-depth interviews (n=30). Structural equation modeling was used to analyze the relationship between psychological factors (self-efficacy, health beliefs, etc.), social support system, clinical indicators and compliance. Thematic analysis was used to explore patients’ subjective experiences and barriers. Results: The study found that compliance was significantly related to multiple factors, including: (1) psychological resilience and self-management ability; (2) family support and quality of doctor-patient communication; (3) disease severity and complications. The established predictive model explained 60% of the variation in compliance. Conclusion: This study shows that improving the compliance of patients with type 2 diabetes with lifestyle changes requires a multi-level intervention strategy that focuses on psychological empowerment, optimization of support systems, and personalized clinical management. This comprehensive model provides new ideas for clinical practice.